Pertanggungjawaban Pemegang Saham Perseroan Perorangan dalam Hal Perseroan Perorangan Mengalami Kerugian Berdasarkan UU No. 11 Tahun 2020 Tentang Cipta Kerja - Muhammad Zulhidayat; Milatul Aslamiyah (Program Studi Hukum Universitas Pamulang, 2021)
This study aims to determine the accountability of shareholders in an individual company in the perspective of Job Creation Law ( as known as Undang-undang Cipta Kerja) and related Government Regulations. This research is a normative juridical study which is based on library-literal research in order to obtain secondary data. Data obtained from legal principles, regulations, and books were analyzed using qualitative methods. This qualitative research produces descriptive-analytical data. The results showed that shareholders in an individual company are only responsible for the shares they own , as long as there are no exempt matters as mentioned in Article 153 J paragraph 2. Based on the results of the research, the authors suggest two things, which are, first for individual company shareholders should run the company in good faith so that the individual company can be utilized properly in accordance with the philosophy of its formation. , secondly, the executive and legislative bodies should be able to make clearer rules regarding the establishment, amendment and discontinuation of individual companies and also supervision due to there is no notary role in the establishment, amendment and dissolution of individual companie.